Social Technologies : Medium Baru untuk Menciptakan Nilai dan Produktivitas bagi Organisasi - Jane, Orpha (Jurnal Administrasi Bisnis, 2013)
Social technologies become more important nowadays. Its not only as a one ofcommunication channel for the firm, but also as a medium to enhance the valueproposition and the productivity of the firm. We can say that Information Communi-cation and Technology was the driver of this phenomenon, especially when Web 2.0has use widely. As the development of social technologies - one of the medium issocial media marketing such as blog, facebook, twitter, etc - become a popular mediain consumerâs life, firm must also see this medium as a strategic tool. This is true,specifically from the result of the research of McKinsey Global Institute (2012) whichattempts to quantify the value of social technologies. The research find that socialtechnologies, when used within and across enterprises, have the potential to raise theproductivity of the high-skill knowledge workers that are critical to performance andgrowth in the 21st century by 20 to 25 percent (MGI, 2012).Keywords: Open innovation, new product development, social technology.